Theban Harbours and Waterscapes Survey, Spring 2016*. Issue 1 (January 2016) - Graham, Angus; Strutt, Kristian D.; Peeters, Jan; Toonen, Willem H. J.; Pennington, Benjamin T.; Emery, Virginia L.; Barker, Dominic S.; Johansson, Carolin
Report on the 2016 spring season of the Theban Harbours and Waterscapes Survey (THaWS). The article discusses the geoarchaeological and geophysical survey along a 3.2 km-long transect starting close to the front of the Temple of Millions of Years of Ay and Horemheb and stretching to the village of Geziret el-Bairat on the West Bank of the Nile.